Suppression of common bacterial blight in mungbean by phylloplane resident Pseudomonas fluorescens strain MBPF-01 alone and in combination with nanocopper - C. MANI, KALYAN K. MONDAL* and (Indian Phytopathology, 2009)
Common bacterial blight is a major threat of mungbean production. The disease is caused by Xanthomonas campestris pv. phaseoli. We evaluate the performance of P. fluorescens strain MBPF-01, an antagonistic phylloplane resident of mungbean, alone or in combination with nanocopper against common bacterial blight. A total of 15 treatments were tested incorporating nanocopper and strain MBPF-01. Though the doses of strain MBPF-01 (3 x 108 cfu ml-1 ) as well as nanocopper (@0.1%) remained same in all treatments but they varied at their time of applications. Two sprays, first with strain MBPF-01 at 0h and 2nd at 7days intervals with nanocopper was found best in suppressing the disease (score 2.18/9.0). We also observe reduced blight intensity in mungbean sprayed with strain MBPF-01 a week before the application of pathogen, suggesting that the suppression is mediated by induced resistance.